Onset Symptom Clusters in Multiple Sclerosis: Characteristics, Comorbidities, and Risk Factors - Ajdacic-Gross, Vladeta; Steinemann, Nina; Horváth, Gábor; Rodgers, Stephanie; Kaufmann, Marco; Xu, Yanhua; Kamm, Christian P.; Kesselring, Jürg; Manjaly, Zina-Mary; Zecca, Chiara; Calabrese, Pasquale; Puhan, Milo A.; et al. (Frontiers in Neurology, 2021)
Background: Multiple sclerosis (MS) symptoms are expected to aggregate in specific patterns across different stages of the disease. Here, we studied the clustering of onset symptoms and examined their characteristics, comorbidity patterns and associations with potential risk factors. Methods: Data stem from the Swiss Multiple Sclerosis Registry, a prospective study including 2063 participants by November 2019. MS onset symptoms were clustered using latent class analysis (LCA). The latent classes were further examined using information on socio-demographic characteristics, MS-related features, potential risk factors and comorbid diseases. Results: The LCA model with six classes (frequencies ranging from 12% to 24%) was selected for further analyses. The latent classes comprised a multiple symptoms class with high probabilities across several symptoms, contrasting with two classes with solitary onset symptoms: vision problems and paresthesia. Two gait classes emerged between these extremes: the gait-balance class and the gait-paralysis class. The last class was the fatigue-weakness-class, also accompanied by depression symptoms, memory and gastro-intestinal problems. There was a moderate variation by sex and by MS types. The multiple symptoms class yielded increased comorbidity with other autoimmune disorders. Similar to the fatigue-weakness class, the multiple symptoms class showed associations with angina, skin diseases, migraine and lifetime prevalence of smoking. Mononucleosis was more frequently reported in the fatigue-weakness and the paresthesia class. Familial aggregation did not differ among the classes. Conclusions: Clustering of MS onset symptoms provides new perspectives on the heterogeneity of MS. The clusters comprise different potential risk factors and comorbidities. They point towards different risk mechanisms.